Efektivitas Bimbingan dan Konseling Islam dengan Hypnotherapy untuk Meningkatkan Leadership Skill Pengurus Pondok Pesantren Nurut Taqwa Bondowoso. (Jurusan Bimbingan dan Konseling Islam, 2017)
Nowadays the face of Indonesia is more alarming. Because some politicians and Indonesian state leaders increasingly loved the Corruption and Collusion and Nepotism (KKN) actions. They are increasingly far from the hopes of the nation and the ideals of the Indonesian freedom fighters. Therefore, to counter the decadence, researchers conducted a study on the use of hypnotherapy to improve leadership skills conducted at Pondok Pesantren Nurut Taqwa Bondowoso, East Java. In addition to efforts to improve the leadership skills of administrators, the core problem examined in this thesis is the desire of researchers to find out the extent of the effectiveness of hypnotherapy in improving leadership skills of Boarding School Boardingmen Nurut Taqwa. In the process of administering hypnotherapy, researchers use the stages of guidance and counseling in general. Meanwhile, to prove whether there is an influence of the guidance on increasing the leadership skills of the board, the researcher uses quantitative research methods that function to uncover the results of all data and facts that have been obtained during this research. While the data collection methods chosen by researchers are in the form of observation, interviews, questionnaires and documentation. After the T-Test was conducted with a significance level of 5%, the results showed that hypnotherapy had an influence in improving the leadership skills of the Boarding School Boarding Board Nurut Taqwa Bondowoso. Therefore, researchers advise all parties concerned and those with positive interests to further explore the use of hypnotherapy in daily life for the achievement of physical and psychological desires.